) 2 1/6 :(8 3/4-5 1/2)=2/3
8 3/4-5 1/2=8 3/4-5 2/4=3 1/4
2 1/6:3 1/4=13/6*4/13=2/3
2)3 17/20:(3 2/5+1 11/15) =3/4
3 2/5+1 11/15=3 6/15+ 1 11/15=4 17/15=
5 2/15
3 17/20:5 2/15=77/20*15/77=3/4
3) (4 3/5-2 1/5):1 1/10 =2 2/11
4 3/5-2 1/5=2 2/5
2 2/5:1 1/10=12/5*10/11=24/11=2 2/11
4)(1 7/10+4/5):1 7/8=1 1/3
1 7/10+4/5=1 7/10+8/10=1 15/10=2 1/2
2 1/2:1 7/8=5/2*8/15=4/3=1 1/3
5) 3 1/8:15/16-1/4
3 1/8:15/16=25/8*16/15=10/3=3 1/3
3 1/3-1/4=3 4/12-3/12=3 1/12
6)1 9/35:(1 1/5+2/3) =33/49
1 1/5+2/3=1 3/15+10/15=1 13/15
1 9/35:1 13/15=44/35*15/28=33/49
7) (11 5/8+7 1/6):3 5/12 =18 19/24
11 5/8+7 1/6=11 15/24+7 4/24=5 1\2
18 19\24:3 5\12=451\24*12\41=11\2=5 1\2
8) (8 7/12-2 5/8):2 1/6=2 3/4
8 7/12-2 5/8=8 14/24-2 15/24=5 23/24
5 23/24:2 1/6=143/24*6/13=11/
В решении.
Объяснение:
Решить квадратное уравнение используя теорему Виета и разложить по формуле квадратного трёхчлена.
Решить:
11) х² - 5х + 6 = 0
По теореме Виета:
х₁ + х₂ = 5;
х₁ * х₂ = 6;
х₁ = 3; х₂ = 2.
12) х² + 5х + 6 = 0
По теореме Виета:
х₁ + х₂ = -5;
х₁ * х₂ = 6;
х₁ = -3; х₂ = -2.
13) х² - 8х + 12 = 0
По теореме Виета:
х₁ + х₂ = 8;
х₁ * х₂ = 12;
х₁ = 4; х₂ = 2.
14) х² - 9х + 18 = 0
По теореме Виета:
х₁ + х₂ = 9;
х₁ * х₂ = 18;
х₁ = 6; х₂ = 3.
15) х² - 7х + 10 = 0
По теореме Виета:
х₁ + х₂ = 7;
х₁ * х₂ = 10;
х₁ = 5; х₂ = 2.
Разложить:
11) х² - 5х + 6;
(х² - 2*х*2,5 + 2,5²) - 2,5² + 6 =
= (х² - 2*х*2,5 + 2,5²) - 6,25 + 6 =
= (х - 2,5)² -0,25;
12) х² + 5х + 6;
(х² + 2*х*2,5 + 2,5²) - 2,5² + 6 =
= (х² + 2*х*2,5 + 2,5²) - 6,25 + 6 =
= (х + 2,5)² - 0,25;
13) х² - 8х + 12;
(х² - 2*х*4 + 4²) - 4² + 12 =
= (х² - 2*х*4 + 4²) - 16 + 12 =
= (х - 4)² - 4;
14) х² - 9х + 18;
(х² - 2*х*4,5 + 4,5²) - 4,5² + 18 =
= (х² - 2*х*4,5 + 4,5²) - 20,25 + 18 =
= (х - 4,5)² - 2,25;
15) х² - 7х + 10;
(х² - 2*х*3,5 + 3,5²) - 3,5² + 10 =
= (х² - 2*х*3,5 + 3,5²) - 12,25 + 10 =
= (х - 3,5)² - 2,25.